1999
DOI: 10.1074/jbc.274.41.29138
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cyclooxygenase-2 by Interferon γ and Transforming Growth Factor α in Normal Human Epidermal Keratinocytes and Squamous Carcinoma Cells

Abstract: Treatment of normal human epidermal keratinocytes (NHEK) with interferon-␥ (IFN-␥

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
143
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 76 publications
(113 reference statements)
10
143
1
1
Order By: Relevance
“…This could be due to the stabilization of COX-2 mRNA (Dean et al, 1999;Lasa et al, 2000;Matsuura et al, 1999;Ridley et al, 1998), or increased transcription of the COX-2 gene (Dean et al, 1999;Subbaramaiah et al, 2000a) as shown in other systems. The fact that the p38 MAPK speci®c inhibitor, SB202190, decreases COX-2 promoter activity suggests that p38 MAPK pathway also plays a role in the transcriptional induction of the COX-2 gene by UVB.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the stabilization of COX-2 mRNA (Dean et al, 1999;Lasa et al, 2000;Matsuura et al, 1999;Ridley et al, 1998), or increased transcription of the COX-2 gene (Dean et al, 1999;Subbaramaiah et al, 2000a) as shown in other systems. The fact that the p38 MAPK speci®c inhibitor, SB202190, decreases COX-2 promoter activity suggests that p38 MAPK pathway also plays a role in the transcriptional induction of the COX-2 gene by UVB.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that bombesin stimulated COX-2 expression in RIE-1 cells transfected with gastrin-releasing peptide receptor involves both ERK and p38 MAPK (17). Similarly, ERK and p38 MAPK pathways mediate the induction of COX-2 expression by transforming growth factor-␣ and interferon-␥ in human epidermal keratinocytes and squamous carcinoma cells (34). JNK and p38 MAPK pathways regulate interleukin-1␤-stimulated COX-2 expression in renal mesangial cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, in cancer microenvironment, cancer-specific or non-specific immune cells that are recruited into cancer sites induce inflammation, a cellular process involving the release of a wide variety of inflammatory mediators including IFN-c [6], subsequently ensuing induction of various cellular proteins such as B7-H1 in cancer cells.…”
Section: Introductionmentioning
confidence: 99%